Tourism 1 : - Walker, Robin (Oxford University Press, 2006)
Focuses on the functional language needed to succeed in the job. This book presents grammar, vocabulary, and skills, contextualized in real work situations. It includes job profiles of real professionals, specialist facts and figures, and quotations. It provides easy-to-understand tips, additional activities for mixed ability classes, and more.